Effects of Switching to the Tobacco Heating System 2.2 Menthol, Smoking Abstinence, or Continued Cigarette Smoking on Biomarkers of Exposure: A Randomized, Controlled, Open-Label, Multicenter Study in Sequential Confinement and Ambulatory Settings (Part 1) - Lüdicke, Frank (Nicotine Tob Res, 2018)
INTRODUCTION: The menthol Tobacco Heating System 2.2 (mTHS) is a newly developed candidate modified-risk tobacco product intended to reduce exposure to the harmful and potentially harmful constituents (HPHCs) of conventional cigarette (CC) smoke. This study examined the impact of switching to mTHS on biomarkers of exposure to HPHCs relative to menthol CCs (mCCs) and smoking abstinence (SA). METHODS: In this three-arm, parallel-group study, 160 Japanese adult smokers (23–65 years; smoking ≥10 mCCs per day) were randomized to mTHS (n = 78), mCC (n = 42), or SA (n = 40) for 5 days in confinement and 85 days in ambulatory settings. Endpoints included biomarkers of exposure to HPHCs, human puffing topography, safety, and subjective effects of smoking measures. RESULTS: After 5 days of product use, the concentrations of carboxyhemoglobin, 3-hydroxypropylmercapturic acid, monohydroxybutenyl mercapturic acid, and S-phenylmercapturic acid were 55%, 49%, 87%, and 89% lower (p < .001), respectively, in the mTHS group than in the mCC group. Other biomarkers of exposure (measured as secondary endpoints) were 50%–94% lower in the mTHS group than in the mCC group on day 5. These reductions in the mTHS group were maintained at day 90, similar to the SA group. Switching to mTHS was associated with changes in human puffing topography (shorter puff intervals and more frequent puffs). The urge-to-smoke and smoking satisfaction levels on day 90 were similar in the mTHS and the mCC groups. CONCLUSION: Switching from mCCs to mTHS significantly reduced exposure to HPHCs relative to continuing smoking mCCs with concentrations similar to those observed following SA in Japanese adult smokers. IMPLICATIONS: This randomized study compared the impact of switching to a modified-risk tobacco product candidate mTHS on biomarkers of exposure to HPHCs of cigarette smoke relative to continuing smoking cigarettes or abstaining from smoking in sequential confinement and ambulatory settings. The study showed that switching to mTHS was associated with significant biomarker reductions within 5 days in confinement, these reductions being maintained throughout the ambulatory setting up to day 90. The results provide evidence that switching to mTHS reduces real-life exposure to HPHCs in adult smokers.